Role of Extracellular Vesicles and microRNAs on Dysfunctional Angiogenesis during Preeclamptic Pregnancies - Escudero, Carlos A.; Herlitz, Kurt; Troncoso, Felipe; Acurio, Jesenia; Aguayo, Claudio; Roberts, James M.; Truong, Grace; Duncombe, Gregory; Rice, Gregory; Salomon, Carlos (Frontiers in Physiology, 2016)
Preeclampsia is a syndrome characterized by hypertension during pregnancy, which is a leading cause of morbidity and mortality in both mother and newborn in developing countries. Some advances have increased the understanding of pathophysiology of this disease. For example, reduced utero-placental blood flow associated with impaired trophoblast invasion may lead to a hypoxic placenta that releases harmful materials into the maternal and feto-placental circulation and impairs endothelial function. Identification of these harmful materials is one of the hot topics in the literature, since these provide potential biomarkers. Certainty, such knowledge will help us to understand the miscommunication between mother and fetus. In this review we highlight how placental extracellular vesicles and their cargo, such as small RNAs (i.e. microRNAs), might be involved in endothelial dysfunction during preeclampsia. Currently only a few reports have addressed the potential role of endothelial regulatory miRNA in preeclampsia. One of the main limitations in this area is the variability of the analyses performed in the current literature. This includes variability in the size of the particles analyzed, and broad variation in the exosomes considered. The quantity of microRNA targets genes suggest that practically all endothelial cell metabolic functions might be impaired. More studies are required to investigate mechanisms underlying miRNA released from placenta upon endothelial function.